Facile fabrication of three-dimensional TiO2 structures for highly efficient perovskite solar cells. (April 2016) - Jang, Segeun; Yoon, Jungjin; Ha, Kyungyeon; Kim, Min-cheol; Kim, Dong Hoe; Kim, Sang Moon; Kang, Seong Min; Park, Sei Jin; Jung, Hyun Suk; Choi, Mansoo
Abstract: The capability of fabricating three dimensional (3-D) nanostructures with desired morphology is a key to realizing effective light-harvesting strategy in optical applications. In this work, we report a novel 3-D nanopatterning technique that combines ion-assisted aerosol lithography (IAAL) and soft lithography that serves as a facile method to fabricate 3-D nanostructures. Aerosol nanoparticles can be assembled into desired 3-D nanostructures via ion-induced electrostatic focusing and antenna effects from charged nanoparticle structures. Replication of the structures with a polymeric mold allows high throughput fabrication of 3-D nanostructures with various liquid-soluble materials. 3-D flower-patterned polydimethylsiloxane (PDMS) stamp was prepared using the reported technique and utilized for fabricating 3-D nanopatterned mesoporous TiO2 layer, which was employed as the electron transport layer in perovskite solar cells. By incorporating the 3-D nanostructures, absorbed photon-to-current efficiency of >95% at 650 nm wavelength and overall power conversion efficiency of 15.96% were achieved. The enhancement can be attributed to an increase in light harvesting efficiency in a broad wavelength range from 400 to 800 nm and more efficient charge collection from enlarged interfacial area between TiO2 and perovskite layers. This hybrid nanopatterning technique has demonstrated to be an effective method to create textures that increase light harvesting and charge collection with 3-D nanostructures in solar cells. Graphical abstract: Highlights: A hybrid nanopatterning method that allows a fabrication of well-ordered 3-D nanostructures was developed. The 3-D nanostructures enhanced light harvesting efficiency in a broad wavelength range. Enlarged interfacial area resulted in improved charge collection. 3-D perovskite solar cell showed 10.30% higher performance than that of conventional one.